In praise of holistic scholarship: A collective essay in memory of Mark Easterby-Smith. Issue 2 (April 2022) - Robinson, Sarah; Contu, Alessia; Elliott, Carole; Gagnon, Suzanne; Antonacopoulou, Elena; Bogolyubov, Pavel; Crossan, Mary; Cunliffe, Ann; Elkjaer, Bente; Graça, Manuel; Kars, Selen; Li, Shenxue; et al.
This collective essay was born out of a desire to honor and remember Professor Mark Easterby-Smith, a founder of the Management Learning community. To do this, we invited community members to share their experiences of working with Mark. The resulting narratives remember Mark as a co-author, co-researcher, project manager, conference organizer, research leader, PhD supervisor, and much more. The memories cover many different aspects of Mark's academic spectrum: from evaluation to research methods to cross-cultural management, to dynamic capabilities, naming but a few. This space for remembrance however developed into a space of reflection and conceptualization. Inspired by the range and extent of Mark's interests, skills, experiences, and personal qualities, this essay became conceptual as well as personal as we turned the spotlight on academic careers and consider alternative paths for Management Learning scholarship today. Using the collective representations of Mark's career as a starting point, we develop, the concept of holistic scholarship, which embraces certain attitudes and orientations in navigating the dialectical spaces and transcending tensions in academic life. We reflect on how such holistic scholarship can be practised in our contemporary and challenging times and what inspiration and lessons we can draw from Mark's legacy.